Recent advances in two-dimensional nanomaterials for photocatalytic reduction of CO2: insights into performance, theories and perspective. Issue 37 (17th September 2020) - Qin, Deyu; Zhou, Yin; Wang, Wenjun; Zhang, Chen; Zeng, Guangming; Huang, Danlian; Wang, Longlu; Wang, Han; Yang, Yang; Lei, Lei; Chen, Sha; He, Donghui
Abstract : This review systematically summarizes the recent advances in two-dimensional nanomaterials for photocatalytic reduction of CO2 and its related mechanisms. Abstract : Global warming and energy shortage are two major stumbling blocks on the road of human social progress, and have gradually aroused a sense of crisis. Artificial photosynthesis is a two-pronged solution to both problems. However, due to the harsh reaction conditions and low efficiency, traditional semiconductors cannot achieve this. Two-dimensional (2D) materials with larger specific surface areas, lower carrier migration distances, more active surface atoms, and higher elastic strain tolerance play a critical role in the solar to chemical energy conversion scheme, and provide a novel methodology for the synthesis of fine chemicals. This review details the principles of photocatalytic reduction of CO2, and highlights the reduction pathways and product selectivity via experimental methods and theoretical calculations. The state-of-the-art achievements of 2D materials in the field of photocatalytic reduction of CO2 are summarized, mainly including material structure, characteristics, and modification strategies to improve the performance of CO2 reduction. And the research on the combination of 2D materials and single atoms is emphasized. Moreover, bottlenecks and challenges in the design and application of 2D materials, as well as prospects of the future development direction, will be highlighted in order to seek new breakthroughs by exploring new materials design solutions.